Emerging role of long noncoding RNAs as regulators of innate immune cell development and inflammatory gene expression - Elling, Roland; Chan, Jennie; Fitzgerald, Katherine A. (European journal of immunology, 2016)
The innate immune system represents the first line of defense during infection and is initiated by the detection of conserved microbial products by germline‐encoded pattern recognition receptors (PRRs). Sensing through PRRs induces broad transcriptional changes that elicit powerful inflammatory responses. Tight regulation of these processes depends on multiple regulatory checkpoints, including noncoding RNA species such as microRNAs. In addition, long noncoding RNAs (lncRNAs) have recently gained attention as important regulators of gene expression acting through versatile interactions with DNA, RNA, or proteins. As such, these RNAs have a multitude of mechanisms to modulate gene expression. Here, we summarize recent advances in this rapidly moving and evolving field. We highlight the contribution of lncRNAs to both the development and activation of innate immune cells, whether it is in the nucleus, where lncRNAs alter the transcription of target genes through interaction with transcription factors, chromatin‐modifying complexes or heterogenous ribonucleoprotein complexes, or in the cytosol where they can control the stability of target mRNAs. In addition, we discuss experimental approaches required to comprehensively investigate the function of a candidate noncoding RNA locus, including loss‐of‐function approaches encompassing genomic deletions, RNA interference, locked nucleic acids, and various adaptions of the CRISPR/Cas9 technology. Long noncoding RNAs (lncRNAs) are emerging as regulators of gene expression, acting through versatile interactions with DNA, RNA, or proteins. We highlight how lncRNAs contribute to the development and activation of immune cells. We also discuss experimental approaches to investigate the function of a candidate noncoding RNA locus.